Recognition of brood-mate vocalizations by Northern Bobwhite (Colinus virginianus) chicks - (:unkn) unknown (My University, 1983)
Unrelated bobwhite quail (Colinus virginianus) chicks were hatched together and raised together. Each chick was tested in an arena with tape recorded separation, contentment and distress calls from a brood-mate and an unfamiliar chick of the same age. Chicks at one, six and 19 days of age gave significantly more separation calls in response to the separation calls of their brood-mates than they gave in response to the separation calls of the strange chicks. Since the chicks were not related, this ability to recognize brood-mate vocalizations is probably learned. Sibling recognition in quail might function in inbreeding avoidance.
Keywords: Northern Bobwhite; Colinus virginianus; behavior; vocalizations